Virtual Library of Cultural Heritage of Central Asian Turks in Written Sources of the XIX Century - Kasimbekov, Abbazbek; Alzhanova, Elmira (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The purpose of this article is the creation of specialized databases virtual university unique full-text library of scientific and educational resources on the cultural heritage of the Central Asian Turks, which are reflected in the written sources of the XIX century and the development of a virtual environment through the establishment of an effective and efficient search of remote access to the necessary sources.